A molecular dynamics study of Wenzel state water droplets on anisotropic surfaces. (15th February 2018) - Ambrosia, Matthew Stanley; Ha, Man Yeong
Highlights: Water droplets in the Wenzel state have larger contact angles at the nanoscale than the Wenzel equation predicts. At the nanoscale water droplets have a larger contact angles when the graphite layers are oriented vertically than horizontally. Water droplets at the nanoscale generally increase as the surface roughness factor increases regardless of the Young contact angle. A logarithmic equation dependent on the surface roughness factor models contact angles on pillared graphite at the nanoscale. Abstract: Some phenomena at the nanoscale are different from those at the macroscale. One of these phenomena is represented by the Wenzel equation which predicts a droplet's contact angle on a textured surface under certain conditions at the macroscale. However, at the nanoscale a different trend is observed in some cases. The Wenzel equation predicts contact angles to decrease as the surface roughness factor increases for droplets with a Young contact angle under 90°. However, for these cases at the nanoscale contact angles become larger as the surface roughness factor increases. In this study molecular dynamic simulations were run to investigate this phenomenon. Five surface energies and five surface roughness factors were considered for a graphite-like surface. Contact angles of nanoscale water droplets on an anisotropic surface with nanoscale texture are plotted and an equation related to the surface roughness factor and Young contact angle that fits the trend is proposed.